Free Radical Scavenging, Cytotoxic Activity, and Antioxidant-Targeted Molecular Docking Analysis of Akar Kusim Besar (Artabotrys sp.) Methanolic Extract from Ketambe, Indonesia - Halimatussakdiah Halimatussakdiah; Ulil Amna; Vivi Mardina; Misdi Misdi (ALCHEMY Jurnal Penelitian Kimia, 2026)
Akar Kusim Besar (Artabotrys sp.), a vine from the Annonaceae family and an orangutan food source in Ketambe (Indonesia), is known to contain diverse bioactive metabolites. This study evaluated the phytochemical profile, antioxidant activity, cytotoxicity, and molecular docking of its methanolic leaf extract. Phytochemical screening confirmed the presence of alkaloids, steroids, terpenoids, saponins, flavonoids, phenolics, and tannins. The extract showed strong radical scavenging activity (IC50 = 100.816 µg/mL) and cytotoxicity against Artemia salina larvae (LC50 = 57.702 µg/mL), indicating potential bioactivity attributable to flavonoids and phenolic compounds. Gas Chromatography-Mass Spectrometry (GC-MS) analysis detected 30 compounds, of which 12 were subjected to molecular docking against human glutathione peroxidase 7 (2P31). Stigmasta-3,5-diene exhibited the strongest binding affinities, while several compounds complied with Lipinski's Rule of Five, supporting their potential druglikeness. Together, these findings suggest that Artabotrys sp. exhibits promising antioxidant and cytotoxic activities, and that molecular docking provides mechanistic insight into its anticancer potential.